2014
DOI: 10.1111/birt.12121
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs, and Decisions of Pregnant Australian Women Concerning Donation and Storage of Umbilical Cord Blood: A Population‐Based Survey

Abstract: Background: Many women giving birth in Australian hospitals can choose to donate their child's umbilical cord blood to a public cord blood bank or pay to store it privately. We conducted a survey to determine the proportion and characteristics of pregnant women who are aware of umbilical cord blood (UCB) banking and who have considered and decided about this option. The survey also sought to ascertain information sources, knowledge and beliefs about UCB banking, and the effect of basic information about UCB on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 16 publications
2
32
0
3
Order By: Relevance
“…However, almost two-thirds of maternity staff members would like additional information about this topic and it is also important for family doctors to have knowledge about UCB as they can communicate this information to prospective parents. According to a recently published study, providing basic information to expecting parents makes them more prone to deciding whether or not to donate UCB (Jordens et al, 2014). A vast majority of staff members in this study would store or recommend storing UCB if feasible and absolutely prefer public banking, revealing a strong altruistic feature of health care providers.…”
Section: Dear Sirmentioning
confidence: 89%
“…However, almost two-thirds of maternity staff members would like additional information about this topic and it is also important for family doctors to have knowledge about UCB as they can communicate this information to prospective parents. According to a recently published study, providing basic information to expecting parents makes them more prone to deciding whether or not to donate UCB (Jordens et al, 2014). A vast majority of staff members in this study would store or recommend storing UCB if feasible and absolutely prefer public banking, revealing a strong altruistic feature of health care providers.…”
Section: Dear Sirmentioning
confidence: 89%
“…This preference suggests that Jordan's public CB bank may find higher acceptance among women at public hospitals but will require robust educational campaigns to raise awareness about the pros and cons of CB banking and the option to donate. Providing more information has been shown to improve perspectives about CB banking …”
Section: Discussionmentioning
confidence: 99%
“…Providing more information has been shown to improve perspectives about CB banking. 20,21 Women at public hospitals may favor father-only informed consent more than women at private hospitals for a variety of reasons. The difference is associated with socioeconomic status, but may also reflect the traditional legal and cultural role of fathers as responsible for the security of and major decisions regarding the children.…”
Section: Discussionmentioning
confidence: 99%
“…Other survey research found similar complexity and variation in responses to ethnicity questions among pregnant women attending antenatal clinics across Greater Sydney. 30 Less than half of the overseas born women, and approximately one-quarter of Australian-born women identified with a cultural group or ethnicity. The majority of women did not.…”
Section: Discussionmentioning
confidence: 99%